2019
DOI: 10.1039/c9ee01238a
|View full text |Cite
|
Sign up to set email alerts
|

High-permeance polymer-functionalized single-layer graphene membranes that surpass the postcombustion carbon capture target

Abstract: A single-layer nanoporous graphene membrane functionalized with CO2-phillic polymers shows extremely fast, selective CO2 transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 52 publications
(55 reference statements)
2
97
0
Order By: Relevance
“…Recently, there has been an increasing recognition of membrane performance targets for post-combustion CO 2 capture. 48 Depending on specific mode of operation, CO 2 /N 2 selectivity is targeted at 20-150 for pressure-driven operation (pressure ratio 5-15), or 4140 when employing a sweep gas. 49 This selectivity must be present in membranes with CO 2 permeabilities of 10 À13 -10 À12 mol m À1 s À1 Pa À1 to be economically-competitive with existing approaches.…”
Section: Papermentioning
confidence: 99%
“…Recently, there has been an increasing recognition of membrane performance targets for post-combustion CO 2 capture. 48 Depending on specific mode of operation, CO 2 /N 2 selectivity is targeted at 20-150 for pressure-driven operation (pressure ratio 5-15), or 4140 when employing a sweep gas. 49 This selectivity must be present in membranes with CO 2 permeabilities of 10 À13 -10 À12 mol m À1 s À1 Pa À1 to be economically-competitive with existing approaches.…”
Section: Papermentioning
confidence: 99%
“…Consequently, this limitation results in a broad PSD. We have shown that N-SLG with broad PSD can be used for gas separation, albeit using an additional gas-selective layer on top of graphene ( 23 , 24 ). Chemical etching technique involving O 2 ( 8 , 25 ), ultraviolet/O 3 ( 17 ), or O 3 ( 19 , 26 ), in principle, can obtain CO 2 -selective nanopores by slowing down the etching kinetics, e.g., using a low temperature or a small concentration of etchant ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because CO 2 , N 2 , and CH 4 have only a small difference in their kinetic diameters (≤0.5 Å), and the state‐of‐the‐art etching techniques are not precise enough to avoid the incorporation of nonselective nanopores in graphene. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%